Early T2 changes predict onset of radiographic knee osteoarthritis: data from the osteoarthritis initiative. Issue 7 (10th March 2014) - Liebl, Hans; Joseph, Gabby; Nevitt, Michael C; Singh, Nathan; Heilmeier, Ursula; Subburaj, Karupppasamy; Jungmann, Pia M; McCulloch, Charles E; Lynch, John A; Lane, Nancy E; Link, Thomas M
Abstract : Objective: To evaluate whether T2 relaxation time measurements obtained at 3 T MRI predict the onset of radiographic knee osteoarthritis (OA). Materials and methods: We performed a nested case–control study of incident radiographic knee OA in the Osteoarthritis Initiative cohort. Cases were 50 knees with baseline Kellgren–Lawrence (KL) grade of 0 that developed KL grade of 2 or more over a 4-year period. Controls were 80 knees with KL grade of 0 after 4 years of follow-up. Baseline T2 relaxation time measurements and laminar analysis of T2 in deep and superficial layers were performed in all knee compartments. The association of T2 values with incident OA was assessed with logistic regression and differences in T2 values by case–control status with linear regression, adjusting for age, sex, body mass index (BMI) and other covariates. Results: Baseline T2 values in all compartments except the medial tibia were significantly higher in knees that developed OA compared with controls and were particularly elevated in the superficial cartilage layers in all compartments. There was an increased likelihood of incident knee OA associated with higher baseline T2 values, particularly in the patella, adjusted OR per 1 SD increase in T2 (3.37 (95% CI 1.72 to 6.62)), but also in the medial femur (1.90 (1.07 to 3.39)), lateral femur (2.17 (1.11 to 4.25)) and lateral tibia (2.23 (1.16 to 4.31)). Conclusions: These findings suggest that T2 values assessed when radiographic changes are not yet apparent may be useful in predicting the development of radiological tibiofemoral OA.